Unidades de paisagem e fragilidade ambiental da bacia hidrográfica do Rio Uru (Goiás) - (:unkn) unknown (Universidade Estadual de Goiás, 2022)
The Cerrado itself is configured such as an imp o rtant environmental complex owing to its territorial extension and its geoenviromental features. Despite of its relevance, the Cerrado area have been so much inhabited, s pecially by agriculture and c attle raising activi ties, causing deep impacts on morphc l imate domains . In this perspective th e current research presents the study goal of the hydrographic basin from Rio Uru (Goiás) located in the central portion of Goiás s ta te and the Cerrado, heading f rom essential conce pts as Landscapes, Geosystem, Landsca p es’ Units, Environmental Fragility an d SIG. The general work target is to evaluate the environmental fragility and basin as its landscapes units throughout traditional mo deling using the increment o f techniques providi ng from multicriterion analysis. The r esearch’s development process began w ith the BHRU geoenvironmental characterization, identifying climatics, geological, geomorphological, pedologicals, morphometricals as pects and the of soil cover, followed by the c rossing of geological, geomorphological and pedological data, which made poss ible the identification of a relief region smoothly waved to flat with meaningful occurrence of Latoso i ls. The Geoenvironmental cha ra cterization allowed, besides the definition of Landscapes Units. At first the Enviro n mental Fragilit ies were mapped to the variable soils, slopes and the usage of a cover. Posteriorly, having in mind the proposal of the systemic analysis, was made the v ar iable fragilities crossing m a ps, and as a re sult, the product, the environmental frag i lity map (traditional modeling) of th e BHRU and of the U P s. The final stage of this work was focused in the fragility development model, having as a start point the mul ti criterion method application AHP (Analytic H ierarchy Process) and the result applicat i on to the basins at all and the lands capes units. As a result, was observed the occurrence of five fragilities classes: Very low, Low, Medium, High and Very High, being p redominants the low and medi u m fragilities. I n this way, the first one, happens more o n flat areas where Latosoils are pred ominant and the second one in hills where the claysoils have more occurrence. The comparative analysis among the modeling applied, co nfirmed the predominance of l aw and medium fr agilities classes occurrence, and the oc c urrence of very low, high and very hi gh in less percentage. The comparison still showed the law and very low fragilities percentage values were close in both modelings an d that, throughout AHP metho d , the others cl asses percentage presented a very reduced data.
Landscape and environmental fragility units of the Uru River hydrographic basin (Goiás)
Keywords: Análise integrada; Modelagem ambiental; Cerrado; Agropecuária; Análise multicritério; Integrated analysis; Environmental modeling; Agriculture and cattle raising.; Multicriterion analysis; GEOCIENCIAS::GEOGRAFIA FISICA; GEOGRAFIA FISICA::GEOMORFOLOGIA; GEOGRAFIA FISICA::CLIMATOLOGIA GEOGRAFICA; GEOGRAFIA FISICA::HIDROGEOGRAFIA; GEOGRAFIA FISICA::GEOCARTOGRAFIA